You are on page 1of 10

Examples of the Fourier Theorem (Sect. 10.3).

I The Fourier Theorem: Continuous case.


I Example: Using the Fourier Theorem.
I The Fourier Theorem: Piecewise continuous case.
I Example: Using the Fourier Theorem.

The Fourier Theorem: Continuous case.


Theorem (Fourier Series)
If the function f : [−L, L] ⊂ R → R is continuous, then f can be
expressed as an infinite series

a0 Xh  nπx   nπx i
f (x) = + an cos + bn sin (1)
2 L L
n=1

with the constants an and bn given by


Z L
1  nπx 
an = f (x) cos dx, n > 0,
L −L L
1 L
Z  nπx 
bn = f (x) sin dx, n > 1.
L −L L

Furthermore, the Fourier series in Eq. (??) provides a 2L-periodic


extension of f from the domain [−L, L] ⊂ R to R.
The Fourier Theorem: Continuous case.
Sketch of the Proof:
I Define the partial sum functions
N
a0 Xh  nπx   nπx i
fN (x) = + an cos + bn sin
2 L L
n=1
with an and bn given by
1 L
Z  nπx 
an = f (x) cos dx, n > 0,
L −L L
1 L
Z  nπx 
bn = f (x) sin dx, n > 1.
L −L L
I Express fN as a convolution of Sine, Cosine, functions and the
original function f .
I Use the convolution properties to show that
lim fN (x) = f (x), x ∈ [−L, L].
N →∞

Examples of the Fourier Theorem (Sect. 10.3).

I The Fourier Theorem: Continuous case.


I Example: Using the Fourier Theorem.
I The Fourier Theorem: Piecewise continuous case.
I Example: Using the Fourier Theorem.
Example: Using the Fourier Theorem.
Example
Find the Fourier series expansion of the function
(
1 + x x ∈ [−1, 0),
f (x) =
1 − x x ∈ [0, 1].

Solution: In this case L = 1. The Fourier series expansion is



a0 X 
f (x) = + an cos(nπx) + bn sin(nπx) ,
2
n=1
where the an , bn are given in the Theorem. We start with a0 ,
Z 1 Z 0 Z 1
a0 = f (x) dx = (1 + x) dx + (1 − x) dx.
−1 −1 0
 x 2  0  x 2  1  1 1
a0 = x + + x− = 1− + 1−
2 −1 2 0 2 2
We obtain: a0 = 1.

Example: Using the Fourier Theorem.


Example
Find the Fourier series expansion of the function
(
1 + x x ∈ [−1, 0),
f (x) =
1 − x x ∈ [0, 1].

Solution: Recall: a0 = 1. Similarly, the rest of the an are given by,


Z 1
an = f (x) cos(nπx) dx
Z 0 −1 Z 1
an = (1 + x) cos(nπx) dx + (1 − x) cos(nπx) dx.
−1 0
Z
1
Recall the integrals cos(nπx) dx = sin(nπx), and

Z
x 1
x cos(nπx) dx = sin(nπx) + 2 2 cos(nπx).
nπ n π
Example: Using the Fourier Theorem.
Example
Find the Fourier series expansion of the function
(
1 + x x ∈ [−1, 0),
f (x) =
1 − x x ∈ [0, 1].

Solution: It is not difficult to see that


1 0 h x 1 i 0
an = sin(nπx) + sin(nπx) + 2 2 cos(nπx)

nπ −1 nπ n π −1
1 1
h x 1 i
1

+ sin(nπx) − sin(nπx) + 2 2 cos(nπx)
nπ 0 nπ n π 0

h 1 1 i h 1 1 i
an = 2 2 − 2 2 cos(−nπ) − 2 2 cos(nπ) − 2 2 .
n π n π n π n π
2  
We then conclude that an = 2 2 1 − cos(nπ) .
n π

Example: Using the Fourier Theorem.


Example
Find the Fourier series expansion of the function
(
1 + x x ∈ [−1, 0),
f (x) =
1 − x x ∈ [0, 1].
2  
Solution: Recall: a0 = 1, and an = 1 − cos(nπ) .
n2 π 2
Finally, we must find the coefficients bn .

A similar calculation shows that bn = 0.

Then, the Fourier series of f is given by



1 X 2  
f (x) = + 1 − cos(nπ) cos(nπx).
2 n2 π 2 C
n=1
Example: Using the Fourier Theorem.
Example
Find the Fourier series expansion of the function
(
1 + x x ∈ [−1, 0),
f (x) =
1 − x x ∈ [0, 1].

1 X 2  
Solution: Recall: f (x) = + 1 − cos(nπ) cos(nπx).
2 n2 π 2
n=1
We can obtain a simpler expression for the Fourier coefficients an .
Recall the relations cos(nπ) = (−1)n , then

1 X 2  n

f (x) = + 1 − (−1) cos(nπx).
2 n2 π 2
n=1

1 X 2  n+1

f (x) = + 1 + (−1) cos(nπx).
2 n2 π 2
n=1

Example: Using the Fourier Theorem.


Example
Find the Fourier series expansion of the function
(
1 + x x ∈ [−1, 0),
f (x) =
1 − x x ∈ [0, 1].

1 X 2  n+1

Solution: Recall: f (x) = + 1 + (−1) cos(nπx).
2 n2 π 2
n=1
If n = 2k, so n is even, so n + 1 = 2k + 1 is odd, then
2
a2k = (1 − 1) ⇒ a2k = 0.
(2k)2 π 2
If n = 2k − 1, so n is odd, so n + 1 = 2k is even, then
2 4
a2k−1 = (1 + 1) ⇒ a 2k−1 = .
(2k − 1)2 π 2 (2k − 1)2 π 2
Example: Using the Fourier Theorem.
Example
Find the Fourier series expansion of the function
(
1 + x x ∈ [−1, 0),
f (x) =
1 − x x ∈ [0, 1].

Solution:

1 X 2  n+1

Recall: f (x) = + 1 + (−1) cos(nπx), and
2 n2 π 2
n=1
4
a2k = 0, a2k−1 = .
(2k − 1)2 π 2


1 X 4
We conclude: f (x) = + cos((2k − 1)πx). C
2 (2k − 1)2 π 2
k=1

Examples of the Fourier Theorem (Sect. 10.3).

I The Fourier Theorem: Continuous case.


I Example: Using the Fourier Theorem.
I The Fourier Theorem: Piecewise continuous case.
I Example: Using the Fourier Theorem.
The Fourier Theorem: Piecewise continuous case.

Recall:
Definition
A function f : [a, b] → R is called piecewise continuous iff holds,
(a) [a, b] can be partitioned in a finite number of sub-intervals
such that f is continuous on the interior of these sub-intervals.
(b) f has finite limits at the endpoints of all sub-intervals.

The Fourier Theorem: Piecewise continuous case.


Theorem (Fourier Series)
If f : [−L, L] ⊂ R → R is piecewise continuous, then the function

a0 Xh  nπx   nπx i
fF (x) = + an cos + bn sin
2 L L
n=1
where an and bn given by
1 L
Z  nπx 
an = f (x) cos dx, n > 0,
L −L L
1 L
Z  nπx 
bn = f (x) sin dx, n > 1.
L −L L
satisfies that:
(a) fF (x) = f (x) for all x where f is continuous;
1 
(b) fF (x0 ) = lim+ f (x) + lim f (x) for all x0 where f is
2 x→x0 x→x0−
discontinuous.
Examples of the Fourier Theorem (Sect. 10.3).

I The Fourier Theorem: Continuous case.


I Example: Using the Fourier Theorem.
I The Fourier Theorem: Piecewise continuous case.
I Example: Using the Fourier Theorem.

Example: Using the Fourier Theorem.


Example (
− 1 x ∈ [−1, 0),
Find the Fourier series of f (x) =
1 x ∈ [0, 1).
and periodic with period T = 2.

Solution: We start computing the Fourier coefficients bn ;


1 L
Z  nπx 
bn = f (x) sin dx, L = 1,
L −L L
Z 0 
Z 1 
bn = (−1) sin nπx dx + (1) sin nπx dx,
−1 0

(−1) h 0 i 1 h 1 i
bn = − cos(nπx) + − cos(nπx) ,

nπ −1 nπ 0

(−1)   1  
bn = −1 + cos(−nπ) + − cos(nπ) + 1 .
nπ nπ
Example: Using the Fourier Theorem.
Example (
− 1 x ∈ [−1, 0),
Find the Fourier series of f (x) =
1 x ∈ [0, 1).
and periodic with period T = 2.
(−1)   1  
Solution: bn = −1 + cos(−nπ) + − cos(nπ) + 1 .
nπ nπ
1   2  
bn = 1 − cos(−nπ) − cos(nπ) + 1 = 1 − cos(nπ) ,
nπ nπ
2 
1 − (−1)n .

We obtain: bn =

2 
1 − (−1)2k , hence b2k = 0.

If n = 2k, then b2k =
2kπ
2
1 − (−1)2k−1 ,
 
If n = 2k − 1, then b2k−1 =
(2k − 1)π
4
hence b2k = .
(2k − 1)π

Example: Using the Fourier Theorem.


Example (
− 1 x ∈ [−1, 0),
Find the Fourier series of f (x) =
1 x ∈ [0, 1).
and periodic with period T = 2.
4
Solution: Recall: b2k = 0, and b2k = .
(2k − 1)π
1 L
Z  nπx 
an = f (x) cos dx, L = 1,
L −L L
Z 0 Z 1
 
an = (−1) cos nπx dx + (1) cos nπx dx,
−1 0
(−1) h 0 i 1 h 1 i
an = sin(nπx) + sin(nπx) ,

nπ −1 nπ 0

(−1)   1  
an = 0 − sin(−nπ) + sin(nπ) − 0 ⇒ an = 0.
nπ nπ
Example: Using the Fourier Theorem.
Example (
− 1 x ∈ [−1, 0),
Find the Fourier series of f (x) =
1 x ∈ [0, 1).
and periodic with period T = 2.
4
Solution: Recall: b2k = 0, b2k = , and an = 0.
(2k − 1)π
Therefore, we conclude that

4 X 1 
fF (x) = sin (2k − 1)π x .
π (2k − 1)
k=1